"Opus metricum": Epic Poem of Neo-Capitalism (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
The following article is a Edoardo Sanguineti’s Opus metricum reinterpretation as an epic poem of modernity. The poetic text, after an initial comparison with the modes of the epos, is approached through three perspectives: an analysis, inspired by the artistic significance treated by Nelson Goodman and Franco Brioschi, of the exemplification implemented by the disfigured poem’s form as a renewed mythopoiesis and storytelling, able to overcome subjectivism and rediscover the paradigm of objectivity; the description of the oral function inherent in the construction and execution of the verse; the theme of the epic foundation, translated in the poetic text into political action expressed by a rediscovery of ritual re-use, which Sini spoke about reading Vico through the Lausberg and Brioschi’s category, within the literary genre.
Keywords: Sanguineti; Laborintus; Erotopaegnia; objectivity; orality; ritualiy